Pelecehan seksual terhadap tokoh perempuan dalam novel Perempuan di Titik Nol karya Nawal El-Saadawi dan The Colour Purple karya Alice Walker - Sulistyorini, Dwi (citeus, 2010)
The purpose of this study is to know what kinds of sexual abuse that have been done to the women figures in the novels “Perempuan di Titik Nol” by Nawal El Saadawi and “The Color Purple” by Alice Walker. Besides, the purpose of the study is to know the impact of sexual abuse that happened to the women. To achieve the objectives above, the study used qualitative design and feminism approach. The re- sult of the studyshows that sexual abuse happened to the leading women figures in the novels from before, during, and after theirmarriage. The kinds of sexual abuse which happened to the leading women figures are gender harrassment, seduction behaviour, sexual bribery, sexual coercion, dan sexual imposition.